2011
DOI: 10.1119/1.3602073
|View full text |Cite
|
Sign up to set email alerts
|

The puzzling reliability of the Force Concept Inventory

Abstract: The Force Concept Inventory (FCI) has influenced the development of many research-based pedagogies. However, no data exists on the FCI's internal consistency or test-retest reliability. The FCI was administered twice to one hundred students during the first week of classes in an electricity and magnetism course with no review of mechanics between test administrations. High KuderRichardson reliability coefficient values, which estimate the average correlation of scores obtained on all possible halves of the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 14 publications
4
45
0
Order By: Relevance
“…The FCI has repeatedly been shown to be an instrument with high internal consistency as measured by Cronbach's alpha [16,21]. All correlations with jrj > 0.3 are positive in Fig.…”
Section: B Correlation Analysismentioning
confidence: 80%
“…The FCI has repeatedly been shown to be an instrument with high internal consistency as measured by Cronbach's alpha [16,21]. All correlations with jrj > 0.3 are positive in Fig.…”
Section: B Correlation Analysismentioning
confidence: 80%
“…We found that both surveys had high [30]. The range for KR-20 is between 0 (indicative of no internal consistency) and 1 (perfect internal consistency).…”
Section: Conceptual Surveysmentioning
confidence: 82%
“…We used the FCI mainly because it is among the most studied and widely used instruments in physics education research [25] and because it is (somewhat surprisingly) reliable [26]. We then calculated average normalized gains for each student in each section [2,27].…”
Section: Force Concept Inventorymentioning
confidence: 99%